2006
DOI: 10.1002/lsm.20355
|View full text |Cite
|
Sign up to set email alerts
|

Local physiological changes during photodynamic therapy

Abstract: Photodynamic therapy creates distinct, measurable changes in tumor oxygen and blood flow during illumination. These physiological changes may ultimately affect treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 37 publications
1
54
0
1
Order By: Relevance
“…The advantage of computerswitched fractionated light delivery with multiple interstitial fibers is that fractionated light can be constantly delivered to the tumor or target organ in various sequences of on/off durations. This may be important as the blood flow and O 2 delivery changes overtime, with a reported initial increase and then decrease (34). Potentially, this change in blood flow and oxygenation can be monitored by sequential illumination and detection in the multifiber array and the duration of on/off sequences adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of computerswitched fractionated light delivery with multiple interstitial fibers is that fractionated light can be constantly delivered to the tumor or target organ in various sequences of on/off durations. This may be important as the blood flow and O 2 delivery changes overtime, with a reported initial increase and then decrease (34). Potentially, this change in blood flow and oxygenation can be monitored by sequential illumination and detection in the multifiber array and the duration of on/off sequences adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this is due to poor control of local photosensitizer concentration, 8,9 the local light dose in the tissue, 10,11 and unknown tissue oxygen concentration. [12][13][14] These factors may lead to large variability in the locally deposited dose of singlet oxygen and other reactive oxidative species.…”
Section: Introductionmentioning
confidence: 99%
“…Some photosensitizers may act as vascular agents at short times after injection and at high fluence rates, where only the vasculature is sufficiently oxygenated, and produce direct cell kill at low fluence rates and long times after injection. 72 An additional level of complexity arises from the fact that the response to PDT is not confined to the cells where the singlet oxygen is deposited but can involve physiological 73 and immunological 74,75 responses as well.…”
Section: Iib5 Pdt Biologymentioning
confidence: 99%